2021
DOI: 10.3390/ph14040299
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Maillard Reaction Products by Lactobacillus gasseri 4M13 Alters the Intestinal Microbiota and Improves Dysfunction in Type 2 Diabetic Mice with Colitis

Abstract: Inflammatory bowel disease is a chronic relapsing disease. Multiple factors can cause inflammatory bowel disease (IBD), including diet, imbalance of the immune system, and impaired intestinal barrier function. Type 2 diabetes mellitus is a complex and chronic metabolic disease caused by a combination of insulin resistance and an ineffective insulin secretory response. The co-occurrence of these two diseases, demonstrating interrelated effects within the gut microbiota, has been frequently reported. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…plantarum, and L. gasseri, amplify the activity of these antioxidant enzymes in T2D mice, thereby minimizing liver damage and oxidative stressthis aligns with our findings. MDA, a marker product of lipid peroxidation, is elevated in T2D patients . CKCC1, CKCC3, and CKCC4 also reduced serum MDA levels in T2D mice (Figure D).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…plantarum, and L. gasseri, amplify the activity of these antioxidant enzymes in T2D mice, thereby minimizing liver damage and oxidative stressthis aligns with our findings. MDA, a marker product of lipid peroxidation, is elevated in T2D patients . CKCC1, CKCC3, and CKCC4 also reduced serum MDA levels in T2D mice (Figure D).…”
Section: Discussionsupporting
confidence: 83%
“…Specifically, IL-6 may hinder glucose-responsive insulin production in islets. TNF-α can deactivate the insulin receptor by phosphorylating its serine residue substrate . Elevated levels of IL-6 and TNF-α exacerbate T2D by promoting insulin resistance, impairing β-cell function, and triggering cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Conjoint analysis of differential genes and microbes found that the abundance of Muricomes was significantly correlated with the expression of NFKBIZ , LYG2 , and IRG1L . The level of Muricomes was abundant in mice with colonitis [ 40 ], and it was associated with liver LDL-cholesterol, which increased in mice fed high-fat food [ 41 ]. The product encoded by NFKBIZ is one of the nuclear I kappa B proteins and an activator of IL-6 production.…”
Section: Discussionmentioning
confidence: 99%
“…According to published studies, a drop in Alloprevotella ( Wang J. et al, 2020 ; Wu et al, 2021 ; Zhang et al, 2021 ; Zhao et al, 2021 ; Hao et al, 2022 ; Liu et al, 2022 ) and an increase in Blautia ( Zhao et al, 2021 ; Bao et al, 2022 ) and Tyzzerella ( Li et al, 2022 ) are found in animal models of in insulin resistance or glucose intolerance. On the other hand, antidiabetic medications and bioactive compounds modulate the gut microbial community of diabetic mouse model, characterized by increased Alistipes ( Hu et al, 2019 ; Jeong et al, 2021 ; Li et al, 2021 ; Wu R. et al, 2022 ) and decreased Anaerotruncus ( Yong et al, 2022 ), Oscillibacter ( Lin et al, 2022 ; Wang et al, 2022 ), Allobaculum ( Jia et al, 2017 ; Shen et al, 2021 ; Xu et al, 2021 ; Ma et al, 2022 ), Acetatifactor ( Wu Y. et al, 2022 ) and Turicibacter ( Zhao et al, 2021 ). These findings coincide with the correlation between microbiota and metabolic phenotypes in our study.…”
Section: Discussionmentioning
confidence: 99%